2019
DOI: 10.1109/access.2019.2919329
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Improve WLAN Indoor Positioning Accuracy Based on DBSCAN-KRF Algorithm From RSS Fingerprint Data

Abstract: WLAN-based indoor positioning algorithm has the characteristics of simple layout and low price, and it has gradually become a hotspot in both academia and industry. However, due to the poor stability of Wi-Fi signals, received signal strength (RSS) fingerprints of some adjacent reference positions are difficult to evaluate similarity when utilizing traditional distance-based calculation methods. By clustering these RSS fingerprints into one region, the commonly utilized KNN algorithm in the past cannot achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…To statistically evaluate the performance of our proposed algorithm and other existing methods, we apply Friedman test, which is used to rank the algorithms' performance. The test statistic suggested by Friedman (14) and F distribution by Iman and Davenport (15) are as follows [33,34] According to the null hypothesis, all the compared algorithms have the same rank. Therefore, the null hypothesis is rejected when the ranks of all algorithms are not equivalent.…”
Section: ) Friedman Test and Post-hoc Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To statistically evaluate the performance of our proposed algorithm and other existing methods, we apply Friedman test, which is used to rank the algorithms' performance. The test statistic suggested by Friedman (14) and F distribution by Iman and Davenport (15) are as follows [33,34] According to the null hypothesis, all the compared algorithms have the same rank. Therefore, the null hypothesis is rejected when the ranks of all algorithms are not equivalent.…”
Section: ) Friedman Test and Post-hoc Analysismentioning
confidence: 99%
“…In the first step, we computed the average ranks of each considering algorithm (i.e., RKNN, ROKNN, RWKNN, and RWOKNN) and the mean rank Rmean of algorithms. Then, we computed the values of TF (14), FF (15), and the critical value of F distribution for significant level of 0.05. With 4 algorithms and 51 data points, the critical value of F distribution is 2.79, which is greater than the mean rank Rmean.…”
Section: ) Positioning Errors Evalutionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBSCAN [11]- [13] is a clustering method used to split the radio map into high-density and low-density clusters, dividing it into n non-overlapping reduced radio maps. Then, in the operational phase, the search has two steps.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the change detection performance, four different scenarios to provoke signal pattern variation are considered. The positioning is executed by the k-NN (Nearest Neighbor) method [36]. From the experimental results, it is found that the similarity metric decreases corresponding to the increment of the positioning error.…”
mentioning
confidence: 99%